Review of technologies for carbon monoxide recovery from nitrogen- containing industrial streams - James, Jebin; Lücking, Leonie E.; van Dijk, H.A.J.; Boon, Jurriaan (Frontiers in Chemical Engineering, 2023)
Carbon monoxide (CO) is an important gas required for various industrial processes. Whether produced directly from syngas or as part of by-product gas streams, valorization of CO streams will play an important role in the decarbonization of industry. CO is often generated in mixtures with other gases such as H2, CO2, CH4, and N2 and therefore separation of CO from the other gases is required. In particular, separation of CO from N2 is difficult given their similar molecular properties. This paper summarizes the current state of knowledge on the four processes for separation of CO from gas mixtures: cryogenic purification, absorption, adsorption and membrane separation. Particular emphasis is placed on technical processes for industrial applications and separation of N2 and CO. Cryogenic processes are not suitable for separation of CO from N2. Absorption developments focus on the use of ionic liquids to replace solvents, with promising progress being made in the field of CO solubility in ionic liquids. Advancements in adsorption processes have focused on the development of new materials however future work is required to develop materials that do not require vacuum regeneration. Membrane processes are most promising in the form of solid state and mixed matrix membranes. In general, there is limited development beyond lab scale for new advancements in CO separation from gas streams. This highlights an opportunity and need to investigate and develop beyond state-of-the-art processes for CO separation at industrial scale, especially for separation of CO from N2.